ETIKA PROFESI GURU PAI DALAM INTERAKSI PEMBELAJARAN DENGAN SISWA - Siti Nurul Kautsar; Imlah Syafira; Irma Maulida; Abd Mukhid; Ahmad Fajar (STKIP Subang, 2026)
This research seeks to investigate how Islamic Education (PAI) teachers put professional ethics into practice when interacting with tenth-grade students at SMK Jaifaq. The ethical conduct of teachers is essential for establishing a supportive learning atmosphere and influencing the moral development and character of students. A descriptive qualitative method was used for this study, gathering data through observations, interviews, and document analysis. The participants included the PAI teacher along with the tenth-grade students. Results show that the PAI teacher has worked to incorporate professional ethics during lessons. This is evident in the teacher's respectful communication, patience, fairness, and initiatives to inspire students. Moreover, the teacher exemplifies strong role modeling through everyday actions. Nonetheless, some challenges emerged, such as varying student characteristics and a lack of discipline exhibited by certain students during lessons. In summary, the role of PAI teachers in applying professional ethics is vital for enhancing positive interactions in the classroom and aiding in the development of students’ character. Therefore, continuous efforts are needed to maintain and enhance teachers’ consistency in applying professional ethics